2019
DOI: 10.12740/pp/91729
|View full text |Cite
|
Sign up to set email alerts
|

Polish version of the Inventory of Complicated Grief – preliminary validation

Abstract: Cel pracyW niniejszym opracowaniu przedstawione zostały wyniki badań dotyczących właściowości psychometrycznych polskiej wersji Inventory of Complicated Grief autorstwa Prigerson I współpracowników (1995).MetodaW badaniach nad adaptacją tego narzędzia wzięło udział 278 osób doświadczających utraty bliskiego członka rodziny lub przyjaciela. Wykorzystano następujące metody badawcze: skala ICG (Inventory of Complicated Grief), skala do badania depresji (BDI), lęku (STAI), zaburzeń po stresie traumatycznym (IES-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
2
6
0
2
Order By: Relevance
“…Regarding the internal consistency of the total scores of the ICG in mourners of deceased due to violence, the indices obtained in the present study indicate that this consistency is excellent (alpha = .927 and omega = .932). These indices are similar to those obtained in many studies with samples of mourners of deceased due to nonviolent causes (range = .93 -.947; Carmassi et al, 2014;Gamba-Collazos & Navia, 2017;Li & Prigerson, 2016;Ludwikowska-Świeboda & Lachowska, 2019;Masferrer et al, 2017;Prigerson et al, 1995). Therefore, the results of this study suggest that the excellent internal consistency of the ICG that is usually obtained in mourners of deceased by non-violent causes is generalized to mourners of deceased by violent causes.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Regarding the internal consistency of the total scores of the ICG in mourners of deceased due to violence, the indices obtained in the present study indicate that this consistency is excellent (alpha = .927 and omega = .932). These indices are similar to those obtained in many studies with samples of mourners of deceased due to nonviolent causes (range = .93 -.947; Carmassi et al, 2014;Gamba-Collazos & Navia, 2017;Li & Prigerson, 2016;Ludwikowska-Świeboda & Lachowska, 2019;Masferrer et al, 2017;Prigerson et al, 1995). Therefore, the results of this study suggest that the excellent internal consistency of the ICG that is usually obtained in mourners of deceased by non-violent causes is generalized to mourners of deceased by violent causes.…”
Section: Discussionsupporting
confidence: 89%
“…On another hand, the factor analyses carried out by Fisher et al (2017) revealed a five-factor structure of the ICG, which does not coincide with those found among the mourners of deceased due to non-violent deaths, which range from one factor (Carmassi et al, 2014;Ludwikowska-Świeboda & Lachowska, 2019;Lumbeck et al, 2012;Prigerson et al, 1995;Simon et al, 2011, full bereaved sample), three factors (Gamba-Collazos & Navia, 2017;Li & Prigerson, 2016;Lifshitz et al, 2022;Limonero et al, 2009), four factors (Masferrer et al, 2017) to six factors (Simon et al, 2011, complicated grief cases). This discrepancy in comparison to Fisher et al's (2017) results could indicate that the characteristics of complicated grief in mourners may be different depending on the cause of the loved one's death, although other differences among mourner samples may also affect the factor structure of the ICG, including the differences in the prevalence of complicated grief.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…The adult hope scale was used to assess divergent validity. According to the results, hope was negatively related to grief due to the loss of Covid-19, which is similar to studies that have shown that people with lower hope experience more severe symptoms of more complicated grief (Ludwikowska-Świeboda & Lachowska, 2019;Yousefi et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…Complicated grief was measured using the Inventory of Complicated Grief (ICG) by Prigerson et al (1995) in its Polish adaptation (Ludwikowska-Świeboda & Lachowska, 2019). The scale comprises 19 statements which describe the feelings and thoughts associated with the death of a loved one.…”
Section: Methodsmentioning
confidence: 99%